The Brain is within the Self and Not Our Entire Self - Zand, Hamid (Journal of NeuroPhilosophy, 2024)
This article explores the true nature of the "self" by excusing the human fear of death and historical attempts to uncover immortality. The human desire for immortality motivates us to study the nature of the self in order to keep it as much as possible. However, the factors that influence self and self-awareness are very complex, and some of them vary each time. Therefore, self-perception changes over time, and recreating it without considering these factors through newly proposed approaches, such as mind uploading or copying the mind into a new brain, may be a challenging endeavor. It seems that despite the complexity and importance of neural networks, the brain cannot fully explain self-awareness. Self-awareness is an emergent property of the brain that arises from its interaction with a set of variable factors that form each moment.